Exploring phytochemicals and their pharmacological applications from ethnomedicinal plants: A focus on Lycium barbarum, Solanacea - Baiken Baimakhanova; Amankeldi Sadanov; Andrey Bogoyavlenskiy; Vladimir Berezin; Lyudmila Trenozhnikova; Gul Baimakhanova; Aibat Ibraimov; Elmira Serikbayeva; Zhalgaskali Arystanov; Tanagul Arystanova; Rakhym Nazakat; Ainura Khammetova; et al. (Heliyon)
Lycium barbarum is a species commonly utilized in dietary supplements and natural healthcare products. Lycium barbarum also referred to as wolfberry or goji berry, are predominantly found in China, Japan, Korea, and North America. Lycium barbarum has a lengthy history as a medicinal and functional food. Recent studies showcasing their exceptional bioac-tive properties have led to an increase in their cultivation and popularity worldwide. Lycium barbarum have been recognized as a valuable source of functional ingredients with promising applications in the food and medical sectors. Lycium barbarum are rich in phytochemical compounds such as polysaccharides, carotenoids, organic acids, carbohydrates (fructose and glucose), phenolic compounds (such as phenolic acids and flavonoids), and vitamins (ascorbic acid). Various biological activities, including antimicrobial, anti-inflammatory, prebiotic, neuroprotective, antidiabetic, and gastroprotective effects, have linked to their consumption. The purpose of this review is to provide a comprehensive overview of the phytochemical components as well as the biological active properties of Lycium barbarum.